The Association of Ethical Judgment of Advertising and Selected Advertising Effectiveness Response Variables - Simpson, Penny M. (Journal of business ethics, 1998)
This study examines the potential effects of unethically perceived advertising executionson consumer responses to the ad. The study found that the unethical perceptions of the advertisement shown significantly and negatively affected all advertising response variables examined in the study.